A new addition to the subfamily Anabropsinae (Orthoptera: Anostostomatidae) from China - Shi, Fuming; Bian, Xun (Zootaxa, 2016)
The paper describes one very interesting genus and species, Brevipenna Shi & Bian gen. nov. and B. falcata Shi & Bian sp. nov.. The genus shares similar characters with macropterous genus Pteranabropsis Gorochov, 1988 and apterous or subapterous genus Apteranabropsis Gorochov, 1988 in following: distributed in Asia, presence both tympana, male ninth abdominal tergite with 1 pair of lobes, which continue with the paired hooks of tenth abdominal tergite, and paraproct specialized with 2 long sclerotized processes. The tegmina and hind wings are short, and right and left ones overlapped. Therefore, we conclude the new genus may be intermediate state between the Pteranabropsis and Apteranabropsis. Perhaps, future study will suggest the three genera be combined. All the material is deposited in the Museum of Hebei University.